Catecholaminergic Innervation of Periventricular Neurogenic Regions of the Developing Mouse Brain - Fauser, Mareike; Weselek, Grit; Hauptmann, Christine; Markert, Franz; Gerlach, Manfred; Hermann, Andreas; Storch, Alexander (Frontiers in Neuroanatomy, 2020)
The major catecholamines – dopamine (DA) and norepinephrine (NE) – are not only involved in synaptic communication, but also act as important trophic factors and might ultimately be involved in mammalian brain development. The catecholaminergic innervation of neurogenic regions of the developing brain and its putative relationship to neurogenesis is thus of pivotal interest. We here determined DA and NE innervation around the ventricular/subventricular zone (VZ/SVZ) bordering the whole ventricular system of the developing mouse brain from embryonic day 14.5 (E14.5), E16.5 and E19.5 until postnatal day zero (P0) by histological evaluation and HPLC with electrochemical detection. We correlated these data with the proliferation capacity of the respective regions by quantification of MCM2+ cells. During development, VZ/SVZ catecholamine levels dramatically increased between E16.5 and P0 with DA levels increasing in forebrain VZ/SVZ bordering the lateral ventricles and NE levels raising in midbrain/hindbrain VZ/SVZ bordering the third ventricle, the aqueduct and the fourth ventricle. Conversely, proliferating MCM2+ cell counts dropped between E16.5 and E19.5 with special focus on all VZ/SVZs outside the lateral ventricles. We detected an inverse strong negative correlation of the proliferation capacity in the periventricular neurogenic regions (log transformed MCM2+ cell counts) with their NE levels (r=-0.932; p<0.001), but not their DA levels (r=0.440; p=0.051) suggesting putative inhibitory effects of NE on cell proliferation within the periventricular regions during mouse brain development. Our data provide a first framework for further demandable studies on the functional importance of catecholamines, particularly NE, in regulating neural stem/progenitor cell proliferation and differentiation during mammalian brain development.